2021
DOI: 10.3390/ijms222413581
|View full text |Cite
|
Sign up to set email alerts
|

Small Extracellular Vesicles Derived from Human Chorionic MSCs as Modern Perspective towards Cell-Free Therapy

Abstract: Mesenchymal stem cells (MSCs) are of great interest to scientists due to their application in cell therapy of many diseases, as well as regenerative medicine and tissue engineering. Recently, there has been growing evidence surrounding the research based on extracellular vesicles (EVs), especially small EVs (sEVs)/exosomes derived from MSCs. EVs/exosomes can be secreted by almost all cell types and various types of EVs show multiple functions. In addition, MSCs-derived exosomes have similar characteristics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Next, to test whether isolated exosomes retain biological functions, we carried out exosome-uptake experiments with epidermal keratinocyte cells, the major cell type of epidermis (Figure f). To visualize bovine milk exosomes with low background and high selectivity, we fluorescently labeled milk exosome membranes with red dyes using an ExoGlow-Membrane labeling kit . The nucleus of the keratinocyte cells was stained with a blue fluorescent dye (DAPI) before the uptake of red-labeled milk exosomes, as shown in Figure g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, to test whether isolated exosomes retain biological functions, we carried out exosome-uptake experiments with epidermal keratinocyte cells, the major cell type of epidermis (Figure f). To visualize bovine milk exosomes with low background and high selectivity, we fluorescently labeled milk exosome membranes with red dyes using an ExoGlow-Membrane labeling kit . The nucleus of the keratinocyte cells was stained with a blue fluorescent dye (DAPI) before the uptake of red-labeled milk exosomes, as shown in Figure g.…”
Section: Resultsmentioning
confidence: 99%
“…Several morphological and biological analyses, specifically nanoparticle tracking analysis (NTA), scanning electron microscopy (SEM), cryo-transmission electron microscopy (TEM), negative-stained TEM, and Western blot analysis, also confirmed that the EPOTF method could isolate bovine milk exosomes in high concentrations with high purity and undeformed shape. To visualize bovine milk exosomes, we also used an ExoGlow-Membrane labeling kit to label the membrane of milk exosomes with a red fluorescent dye, which is absorbed into epidermal keratinocyte cells . Finally, we optimized the appropriate isolation conditions to maintain proper permeability, long-term filtration efficiency, and low susceptibility to flow pressure and Joule heating.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to exosomes secreted by cultured AFSCs [ 24 ], small extracellular vesicles obtained from chorionic-derived MSCs were also characterized to explore their potential in OA treatment [ 49 ]. Other biomaterials or biologics derived from human placentas demonstrated reduced pain, cartilage damage, and inflammation without product-related adverse findings in animal models of OA [ 18 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…EVs contain and protect useful biological information, including proteins, lipids, lncRNA, mRNAs, and regulatory miRNA [ 140 ]. Janockova et al demonstrated that small EVs and their content can be taken-up by different types of cells isolated from tissues associated with OA (SF, osteoblasts and periosteum-derived MSCs) suggesting their prospective role in the treatment of OA [ 142 ]. It is thought that EVs have the ability to act as paracrine effectors and mediators of cell-to-cell communication [ 62 ].…”
Section: Potential Ev-associated Biomarkers Of Osteoarthritismentioning
confidence: 99%